Večjezični možgani - Rossi, Eleonora (Jezik in slovstvo, 2009)
Bilingual aphasia is still a field of research under construction. On the one hand, there are considerably few studies which describe cases of bilingual aphasia, despite the fact that more and more cases need (and will need) attention in the clinical reality. On the other hand, the guidelines to deal with the assessment and the therapy of those increasing number of cases is still poor. The goal of this paper is to give a historical background of the definitions given about bilingual aphasia and outline the relevant theoretical models. The description of a single case study will be used to illustrate one case of recovery of the second language in a bilingual aphasic speaker. Some general guidelines for treatment will be proposed.
Keywords: psiholingvistika; sociolinguistics; sociolingvistika; bilingualism; dvojezičnost; spomin; memory; afazija; dvojezična afazija; lokacija jezika v možganih